From Jonah to Pinocchio: on the Biblical Origins of a long-lasting Motif in Sea Epics (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2021)
This paper (1) analyzes the motif of the fish swallowing Jonah in light of similar episodes attested in Hellenistic Greek epics and other Hellenistic literary traditions and myths. In light of this evidence, it proposes a possible context in which the biblical story emerged. In addition, the paper (2) also analyzes how this motif developed in early Jewish and early Christian traditions, showing how both traditions shape this motif to fit familiar patterns of sea epics. From a larger perspective, this study both allows us (3) to rethink the attitudes towards seafaring that were traditionally attributed to Judeans in Hellenistic times, while also (4) offering new suggestions as to how we might reposition the epic genre in the Hebrew Bible.